IDH1 as a Cooperating Mutation in AML Arising in the Context of Shwachman-Diamond Syndrome - Mourad, Stéphanie; Bilodeau, Mélanie; Roussy, Mathieu; Laramée, Louise; Boulianne, Luc; Rouette, Alexandre; Jouan, Loubna; Gendron, Patrick; Duval, Michel; Teira, Pierre; Hébert, Josée; Bittencourt, Henrique; et al. (Frontiers in Oncology, 2019)
Shwachman-Diamond syndrome (SDS) is a rare and systemic disease mostly caused by mutations in the SBDS gene and characterized by pancreatic insufficiency, skeletal abnormalities and a bone marrow dysfunction. In addition, SDS patients are predisposed to develop myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML), typically during adulthood and associated with TP53 mutations. Although most SDS diagnoses are established in childhood, the nature and frequency of serial bone marrow cell investigations during the patients’ lifetime remain a debatable topic. The precise molecular mechanisms leading to AML progression in SDS patients have not been fully elucidated because the patient cohorts are small and most disease monitoring is conducted using standard histological and cytogenetic approaches. Here we report a rare case of a patient with SDS who was diagnosed with AML at 5 years of age and survived. Intermittent neutropenia preceded the AML diagnostic but serial bone marrow monitoring according to the standard of care revealed no cytogenetic anomalies nor signs of clonal hematopoiesis. Using next generation sequencing approaches to find cytogenetically cryptic pathogenic mutations, we identified the cancer hotspot mutation c.394C>T/p.Arg132Cys in IDH1 with high variant allelic frequency in bone marrow cells, suggesting clonal expansion of a major leukemic clone karyotypically normal, in the SDS-associated AML. The mutation was somatic and likely occurred at the leukemic transformation stage, as it was not detected in a matched normal tissue nor in bone marrow smear prior to AML diagnosis. Gain-of-function mutations in IDH1, such as c.394C>T/p.Arg132Cys, create a neo-activity of isocitrate dehydrogenase 1 converting α-ketoglutarate into the oncometabolite D-2-hydroxyglutarate, inhibiting α-ketoglutarate-dependent enzymes, such as histone and DNA demethylases. Overall, our results suggest that along with previously described abnormalities such as TP53 mutations or monosomy7, 7q-, which are all absent in this patient, additional mechanisms including IDH1 mutations drive SDS-related AML and are likely associated with variable outcomes. Sensitive techniques complementary to standard cytogenetics, such as unbiased or targeted panel-based next generation sequencing approaches, warrant testing for monitoring of myelodysplasia, clonal hematopoiesis, and leukemia in the context SDS. Such analyses would also assist treatment decisions and allow to gain insight into the disease biology.